2017
DOI: 10.1021/acs.jafc.7b01762
|View full text |Cite
|
Sign up to set email alerts
|

Meroterpenoids with Antitumor Activities from Guava (Psidium guajava)

Abstract: Psidium guajava L., a species native to South America, has been widely cultivated in the tropical and subtropical areas of China for its popular fruits. The preliminary analysis by liquid chromatography-ultraviolet (LC-UV) indicated the presence of meroterpenoids in the fruits of P. guajava (guava). Subsequent fractionation of the petroleum ether extract resulted in the identification of two new meroterpenoids, psiguajavadials A (1) and B (2), together with 14 previously described meroterpenoids (3-16). Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 27 publications
2
40
1
1
Order By: Relevance
“…The annotation results were confirmed by commercial authentic standards (Table 1, compounds 2, 5, and 6) or a purification process (1). Guajadial B exhibited antitumor activity in five human cancer cell lines (HCT116, CCRFCEM, DU145, Huh7, and A549) at an IC50 value of 150 nM [28]. Medicagenic acid has been identified as an antifungal agent against Pyricularia pryzae (minimum inhibitory concentration (MIC) = 0.01 mg/mL and minimum fungicidal concentration (MFC) = 0.03 mg/mL) [29].…”
Section: Discussionmentioning
confidence: 99%
“…The annotation results were confirmed by commercial authentic standards (Table 1, compounds 2, 5, and 6) or a purification process (1). Guajadial B exhibited antitumor activity in five human cancer cell lines (HCT116, CCRFCEM, DU145, Huh7, and A549) at an IC50 value of 150 nM [28]. Medicagenic acid has been identified as an antifungal agent against Pyricularia pryzae (minimum inhibitory concentration (MIC) = 0.01 mg/mL and minimum fungicidal concentration (MFC) = 0.03 mg/mL) [29].…”
Section: Discussionmentioning
confidence: 99%
“…These functions of guava extracts are related to numerous bio-active molecules such as beta-caryophyllene oxide, vitamins, tannins, phenolic compounds, flavonoids and triterpenoid acids [2,[4][5][6]. Previous studies have demonstrated that guava extracts can inhibit cell growth in various cancers such as lung cancer, colorectal carcinoma, myeloid leukemia, squamous cell carcinoma, myeloma, cervical cancer and gastric cancer [3,7,8]. However, the mechanisms induced by guava extracts that result in anti-cancer activities remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…and He et al [33]. These compounds showed interesting anti-cancer activity in vitro against cervical cancer, gastric adenocarcinoma and breast cancer cells, while berkeleyacetal C [34,35,36] and rubratoxin B [37,38,39] showed anti-inflammatory activity and anticancer in vitro.…”
Section: P Purpurogenum Extract Showed Activity Against Ehrlich's Somentioning
confidence: 97%